Zoom Meeting Practices During the Covid-19 Era - Ilham Tri Maulana; Fadil Firdian; Liranti Rahmelina; Zainul Efendy; Rajab Rajab; Elisa Daniati (Journal International Inspire Education Technology, 2022)
Abstract— This study aims to see the practicality of using the zoom meeting application for student learning at Madrasah Diniyah Takmiliyah Awwaliyah Jabal Nur Mosque, Padang City. This Zoom Meeting is used to be able to assist teachers and students in the learning process in tahfizh learning. The research method used is a qualitative method. The type of data is primary data where the data is provided by media experts, teachers and students. The data analysis technique used is descriptive data analysis technique, namely by describing the practicality of using zoom meetings for tahfizh learning. The results of the study based on the response from the teacher of the practical zoom meeting application used for tahfizh learning with an average total score of 89%. The results of the study based on the response from the students, the zoom meeting application is quite practical which is used for tahfizh learning with an average total score of 74.88%. Based on the results of this study, it is concluded that the zoom meeting application is practical to be used as a learning medium in tahfizh learning at Madrasah Diniyah Takmiliyah Awwaliyah Jabal Nur Padang City. The results of this study are also recommended for other Diniyah Takmiliyah Awwaliyah Madrasah.